Pola Penggunaan Obat Antipsikotik pada Pasien Skizofrenia di Puskesmas Rawat Jalan Alah Air Kabupaten Kepulauan Meranti - Husnawati - Husnawati (LPPM Universitas Abdurrab, 2022)
The high number of schizophrenic patients at the Puskesmas Alah Air needs attention, one of which is the pattern of treatment. This study aims to determine the pattern of the use of antipsychotic drugs at the Puskesmas Alah Air, Tebing Tinggi District, Kepulauan Meranti. This research is an observational study with a descriptive design. The data source in this study was patient medical record data during January to December 2021 at the Puskesmas Alah Air. The study sample was 81 patients who met the inclusion criteria. The results showed that the majority of schizophrenic patients were male (74.1%), with an early adult (18-40) year as many as 60.5%. Based on the most widely used antipsychotic drugs, the typical antipsychotic group with halloperidol was 71.6%. Based on the route of administration, 100% of the drugs were given orally. Based on the generic name and trade name, 100% of the drugs used are generic. Based on single and combination therapy, the results obtained are combination therapy, which is 90.1% and the most combinations are typical antipsychotics with typical. The conclusion of this study shows that the pattern of drug use is to use a typical generic antipsychotic orally in a combination form